A new sampling device for metabarcoding surveillance of port communities and detection of non-indigenous species - Jesús Zarcero; Adrià Antich; Marc Rius; Owen S. Wangensteen; Xavier Turon (iScience, 2024)
Summary: Metabarcoding techniques are revolutionizing studies of marine biodiversity. They can be used for monitoring non-indigenous species (NIS) in ports and harbors. However, they are often biased by inconsistent sampling methods and incomplete reference databases. Logistic constraints in ports prompt the development of simple, easy-to-deploy samplers. We tested a new device called polyamide mesh for ports organismal monitoring (POMPOM) with a high surface-to-volume ratio. POMPOMS were deployed inside a fishing and recreational port in the Mediterranean alongside conventional settlement plates. We also compiled a curated database with cytochrome oxidase (COI) sequences of Mediterranean NIS. COI metabarcoding of the communities settled in the POMPOMs captured a similar biodiversity than settlement plates, with shared molecular operational units (MOTUs) representing ca. 99% of reads. 38 NIS were detected in the port accounting for ca. 26% of reads. POMPOMs were easy to deploy and handle and provide an efficient method for NIS surveillance.